TANTANGAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMAHAMI STANDAR PROSES DI SEKOLAH MENENGAH PERTAMA - Nisa Kholifah; Chaerul Rochman; Ida Farida; Hasan Basri (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
This study aims to analize understanding of the educational process standards in PAI and non-PAI teachers. This is important to discuss in order to know the understanding of the standard education process in junior high. The method used in this study uses descriptive quantitative research including five PAI teachers and five Non PAI teacher and this study describes the teacher's understanding of the Process Standard indicators through the calculation of perception on each of the Indicators. The instrument used was a questionnaire about understanding Standard Process. The conclusion of this research is that both of them have a high level of understanding (very good) but the difference is the challenges faced by each teacher. Both PAI Teachers and Non PAI Teachers.